Answer:
y = 2x + 2
Step-by-step explanation:
The general form
is;
y = mx + b
where m is the slope and b is the y-intercept
so we have;
y = mx + 2
To get m, substitute the point (-1,0)
So we have
0 = -m + 2
m = 2
So the equation is;
y = 2x + 2
The answer to 1/2y+3/2=3y+4 is y= -1
Answer:
<h2><u>Given</u><u> </u><u>:</u><u>-</u></h2>
- There are 595 total students in the school .
- 60% of the total students voted to be the falcons .
![\large\bf{\underline{To \:find }}](https://tex.z-dn.net/?f=%5Clarge%5Cbf%7B%5Cunderline%7BTo%20%5C%3Afind%20%7D%7D)
- How many students voted not to be in falcon ?
![\large\bf{\underline{Therefore }}](https://tex.z-dn.net/?f=%5Clarge%5Cbf%7B%5Cunderline%7BTherefore%20%20%7D%7D)
⟹ 100 - 60 = 40
- 40% of the total students voted not be in falcon
![\large\bf{\underline{Hence }}](https://tex.z-dn.net/?f=%5Clarge%5Cbf%7B%5Cunderline%7BHence%20%7D%7D)
⟹ 40% of 595
![= \frac{40}{100} \times 595](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7B40%7D%7B100%7D%20%20%5Ctimes%20595)
![=2 \times 119](https://tex.z-dn.net/?f=%3D2%20%5Ctimes%20119)
![= 238](https://tex.z-dn.net/?f=%20%3D%20238)
![\bf{\underline{So , 238 \: students \:voted \:not\:to \:be\:in\: falcon }}](https://tex.z-dn.net/?f=%5Cbf%7B%5Cunderline%7BSo%20%2C%20238%20%5C%3A%20students%20%5C%3Avoted%20%5C%3Anot%5C%3Ato%20%5C%3Abe%5C%3Ain%5C%3A%20falcon%20%7D%7D)
Your statemtent is incomplete.
I found the samestatment with the complete words: <span>Simplify
completely quantity x squared minus 3 x minus 54 over quantity x
squared minus 18 x plus 81 times quantity x squared plus 12 x plus </span>36 over x plus 6
Given that your goal is to learn an be able to solve any similar problem, I can teach you assuming that what I found is exactly what you need.
x^2 - 3x - 54 x^2 + 12x + 36
------------------ x ---------------------
x^2 - 18x + 81 x + 6
factor x^2 - 3x - 54 => (x - 9)(x + 6)
factor x^2 - 18x + 81 => (x - 9)^2
factor x^2 + 12x + 36 = (x + 6)^2
Now replace the polynomials with the factors=>
(x - 9) (x + 6) (x + 6)^2 (x + 6)^2 x^2 + 12x + 36
------------------------------ = --------------- = --------------------
(x - 9)^2 (x + 6) (x - 9) x - 9